Optimal Physical Condition for Youth Soccer Players - Zainuddin, M. Said (International Journal of Education, Vocational and Social Science, 2024)
This study investigates the physical characteristics of high-level youth soccer players and how these characteristics vary by playing position. Utilizing a cross-sectional research design, data were collected from 123 players aged 15, categorized into positions such as goalkeeper, defender, midfielder, and forward. Various physical parameters, including speed, agility, and aerobic and anaerobic capacity, were assessed through standardized tests. The findings reveal significant differences in physical performance across positions, with midfielders demonstrating superior agility and aerobic fitness compared to goalkeepers and defenders. These results underscore the necessity for tailored training programs that address the specific demands of each position to enhance overall athletic performance. By understanding these differences, coaches can optimize training regimens, ultimately aiding young athletes in reaching their full potential. This research contributes valuable insights for sports practitioners focused on youth development in soccer.